The effects of continuous glucose monitoring system on patient outcomes and associated costs in a real‐world setting. Issue 5 (24th February 2021) - Triki, Noa; Yekutiel, Naama; Levi, Lilly; Azuri, Joseph
Abstract: Aims: Continuous glucose monitoring system (CGMS) technologies may alert unaware hypoglycaemia or near hypoglycaemia events. However, costs are a significant concern in general CGMS use. This study describes the real‐world effects of both clinical outcomes and associated costs in a major Health Maintenance Organization, 1 year following preauthorization of CGMS for each patient. Methods: Cohort study. Type 1 diabetes patients who were preauthorized CGMS were identified, and their medical records during the year before preauthorization were compared to the following year. Data were collected for glucose control, medical services utilization and related costs. Results: We identified 524 eligible patients, 57% males. Adherence to CGMS use was improved by age. The proportion of patients reaching HbA1c  < 7.5% (58 mmol/mol) increased in the high‐adherence group and decreased in the low‐adherence group. There were no significant changes in outpatient medical services utilization. However, there was a decrease in emergency room visit rates (30%–19%, p  < 0.01) and hospitalization rates (22%–12%, p  < 0.01) with the highest decrease among the high‐adherence group. Hospitalization duration also decreased. However, the total costs per patient were higher as CGMS adherence increased. Conclusion: Continuous glucose monitoring system technologies have the potential of both improving blood glucose control and reducing inpatient utilization. However, CGMS technologies costs may put a significant burden on healthcare systems.